Proton therapy for thoracic malignancies: a review of oncologic outcomes. Issue 2 (1st February 2021) - Patel, Nirav V; Yu, Nathan Y; Koroulakis, Antony; Diwanji, Tejan; Sawant, Amit; Sio, Terence T; Mohindra, Pranshu
ABSTRACT: Introduction : Radiotherapy is an integral component in the treatment of the majority of thoracic malignancies. By taking advantage of the steep dose fall-off characteristic of protons combined with modern optimization and delivery techniques, proton beam therapy (PBT) has emerged as a potential tool to improve oncologic outcomes while reducing toxicities from treatment. Areas covered : We review the physical properties and treatment techniques that form the basis of PBT as applicable for thoracic malignancies, including a brief discussion on the recent advances that show promise to enhance treatment planning and delivery. The dosimetric advantages and clinical outcomes of PBT are critically reviewed for each of the major thoracic malignancies, including lung cancer, esophageal cancer, mesothelioma, thymic cancer, and primary mediastinal lymphoma. Expert opinion : Despite clear dosimetric benefits with PBT in thoracic radiotherapy, the improvement in clinical outcomes remains to be seen. Nevertheless, with the incorporation of newer techniques, PBT remains a promising modality and ongoing randomized studies will clarify its role to determine which patients with thoracic malignancies receive the most benefit. Re-irradiation, advanced disease requiring high cardio-pulmonary irradiation volume and younger patients will likely derive maximum benefit with modern PBT.